2013
DOI: 10.1093/bja/aet050
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone, light anaesthesia, and tight glucose control (DeLiT) randomized controlled trial

Abstract: Among our three interventions, dexamethasone alone reduced inflammation. However, no intervention reduced the risk of major morbidity or 1 yr mortality. TRIAL REGISTRATION IDENTIFIER: NCT00433251 at www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 47 publications
1
19
0
3
Order By: Relevance
“…This is important to acknowledge since dexamethasone itself may predispose to infection, which we have shown in previous facial fracture studies [11][12][13]. The same phenomenon was also shown by Abdelmalak et al who observed a higher rate of infections in vascular surgery patients with perioperatively administered dexamethasone, despite significantly decreased CRP levels [15]. We consider the use of dexamethasone in association with surgical treatment of facial fracture to be beneficial in selected patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is important to acknowledge since dexamethasone itself may predispose to infection, which we have shown in previous facial fracture studies [11][12][13]. The same phenomenon was also shown by Abdelmalak et al who observed a higher rate of infections in vascular surgery patients with perioperatively administered dexamethasone, despite significantly decreased CRP levels [15]. We consider the use of dexamethasone in association with surgical treatment of facial fracture to be beneficial in selected patients.…”
Section: Discussionsupporting
confidence: 80%
“…As a negative consequence, however, surgical wound healing may be retarded, and the risk for surgical site infection may increase [11][12][13]. The postoperative increase in CRP may be attenuated by glucocorticoids [14,15]. How and to what extent perioperatively administered glucocorticoids affect postoperative CRP levels after surgery of facial fractures in particular remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious complications were not evaluated. Next, secondary interim analyses of 381 patients enrolled in the Dexamethasone, Light Anesthesia and Tight Glucose Control (DeLiT) trial did not demonstrate a relationship between intensive insulin therapy and a composite morbidity and mortality endpoint [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Institutional review board approval (Cleveland Clinic Institutional Review Board, approval number 07-10) and written informed consent were obtained. We report a post hoc analysis of the results obtained during a previously published study in which we evaluated the effects of dexamethasone, light anaesthesia and tight glucose control on surgical outcomes in non-cardiac surgery patients-the Dexamethasone, Light Anaesthesia and Tight Glucose Control (DeLiT) Trial (Clinical trials.gov identifier: NCT00433251) 15,16 .…”
Section: Methodsmentioning
confidence: 99%